Ricci-pseudosymmetric almost $α$-cosymplectic $(k,μ , u)$-spaces admitting Ricci solitons - Uygun, Pakize; Atçeken, Mehmet; Mert, Tugba (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 514.7We study some types of Ricci pseudosymmetric $α$-cosymplectic $(k,μ , u)$-spaces whose metric admits Ricci solitons. We present some results obtained for Ricci solitons on Ricci pseudosymmetric, projective Ricci pseudosymmetric, concircular Ricci pseudosymmetric, and $W_1$-Ricci pseudosymmetric spaces. Some results on almost $α$-cosymplectic $(k,μ , u)$-spaces are also presented. Finally, we give an example for the 5-dimensional case.